The dual role of the CD95 and CD95L signaling pathway in glioblastoma - Zhang, Yanrui; Jin, Taian; Dou, Zhangqi; Wei, Boxing; Zhang, Buyi; Sun, Chongran (Frontiers in Immunology, 2022)
CD95, a death receptor on the surface of cells, when binding with its homologous ligand CD95L, transduces a cascade of downstream signals leading to apoptosis, which is crucial for immune homeostasis and immune surveillance. Although the binding of CD95 and CD95L classically induces programmed cell death, most tumor cells show resistance to CD95L-induced apoptosis. In some cancers, such as glioblastoma, CD95-CD95L can exhibit paradoxical functions that promote the growth of the tumors by inducing inflammation, regulating immune cell homeostasis and/or promoting cell survival, proliferation, migration, and maintaining the stemness of cancer cells. In this review, some possible mechanisms such as the expression of apoptotic inhibitor proteins, the decreased activity of downstream elements, the production of non-apoptotic soluble CD95L, and the non-apoptotic signals replacing apoptotic signals in cancer cells were summarized. In addition, CD95L is expressed by other types of cell such as endothelial cells, polymorphonuclear myeloid-derived suppressor cells, cancer-associated fibroblasts and tumor-associated microglia, and macrophages which were educated by the tumor microenvironment and can induce apoptosis of tumor-infiltrating lymphocytes which can recognize and kill cancer cells. The dual role of the CD95-CD95L system makes the strategies of targeted therapies against CD95 or CD95L in glioblastoma difficult and controversial. In this review, we also discuss the current situation and perspective view of the clinical trials on glioblastoma based on CD95-CD95L signaling pathway.